Homestay Operators' Experiences in Initiating and Developing Homestay Enterprises - Kanel, Chet Nath; Bhattarai, Prakash C.; Gnawali, Laxman (Journal of Tourism and Himalayan Adventures, 2024)
Community homestay development is one of the strategies to culture-based accommodation, mostly in the rural and remote settlements in Nepal. Homestay tourism has been in practice for more than two decades, and it is rapidly spreading in many parts of the country. This article attempts to bring the views and experiences of community homestay operators regarding their understanding, awareness, perceived benefits, and homestay initiation and development practices from Mahabharat Hills of Bagmati Province. Ethnographic field observations and 'bhalakusari' (in-depth talk) were the dominant methods applied during the data collection process. The findings suggest that due to multiple types of perceived as well as experienced benefits from community homestay tourism, locals have enthusiastically learned and adopted homestay enterprising, in which local-level institutional facilitation and support activities have become main motivators in the processes. In such areas, gradual increase in external facilitation, exposure and capacity development endeavors, increasing tourist arrivals, and wide ranges of direct and indirect economic, socio-cultural, and environmental benefits are visible. All these factors have encouraged the locals to engage and expand community homestay development initiatives in their areas. Despite multiple positive facets of homestay tourism, there exist some challenges too. The article also suggests some policy and practice-level implications.